Comparative Performance of Aonla (Emblica officinalis G.) Cultivars under Parbhani Condition - Maholiya, Bantesh Kumar; Prasad, Heerendra; Gupta, Arun Kumar; Thakur, Manish; Solanki, Shivendu Pratap Singh (International Journal of Bio-resource and Stress Management, 2023)
The present investigation was carried out at the Department of Horticulture, college of Agriculture, Marathwada Krishi Vidyapeeth, Parbhani Maharastra during year 2009-2010 to evaluate “Comparative Performance of Aonla (Emblica officinalis G.) Cultivars under Parbhani Condition”. The experiment was laid out in Randomized Block Design (RBD) with four varieties and it was replicated five times.The study comprises of one experiment in which aonla trees under investigation to yield and fruit physico-chemical characters. The highest yield of fruits per tree was recorded in Kanchan (3459 fruits tree-1 and 99.79 kg fruits tree-1). Higher size of fruits was observed in NA-7, whereas, small size fruits were observed in Krishna. Maximum weight of fruit was recorded in NA-7 (42.44 g). Maximum pulp percentage (96.74%) and minimum fibre percentage (0.66%) were recorded in Chakaiya. Kanchan variety recorded high TSS (11.90%) and maximum acidity (2.13%) whereas, minimum TSS and acidity percentage were recorded in NA-7 (1.79% acidity), respectively. Maximum and minimum ascorbic acid content were observation in Chakaiya (607.48 mg 100 g-1) and NA-7 (362.32 mg 100 g-1), respectively. Highest total sugar per cent (4.68) estimated in Krishna. However, on the basis of result obtained in present study, it can be suggested that Kanchan is superior variety under agro-climatic condition of Parbhani due to its performance regarding the highest yield with good quality fruits.